Isolated Gastrointestinal Metastasis of Breast Carcinoma: A Case Report. (1st June 2010) - Titi, M. A.; Anabtawi, A.; Newland, A. D.
Abstract : Purpose . Gastrointestinal tract is one of the rare locations for breast cancer metastasis. This paper shows such metastasis may occur even in the absence of breast metastasis in other more common locations. Case Report . A 64-year old female was admitted to the hospital with abdominal discomfort and diarrhea. She had breast carcinoma treated 7 years previously with normal follow-up since. Colonoscopy showed hepatic flexure thickening that was confirmed to be breast metastasis. Staging investigations showed upper and lower gastrointestinal tract metastasis with negative findings elsewhere. Conclusion . Although more common causes for gastrointestinal symptoms should be excluded, however, a high index of suspicion of metastatic breast cancer is needed when such patients develop gastrointestinal symptoms.